Pesan Dakwah Dalam Webtoon JOYful Delight Karya Chairunnisa Puspasari (Analisis Semiotika Charles Sanders Pierce) - Lestari, Astri; Saefulloh, Uwoh; Fatoni, Uwes (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This paper aims to determine the representation, object, and interpretation of da'wah messages in the JOYful Delight webtoon. The method used is a descriptive qualitative approach using Charles Sanders Pierce's semiotic analysis which aims to examine signs or symbols in the form of illustrated images or texts in the JOYful Delight webtoon, by looking at signs based on representations, objects, and interpretations. The results and discussion of this study indicate that the JOYful Delight webtoon contains Islamic values, namely da'wah messages that can make readers understand things that are closely related to Islamic teachings, namely the Qur'an and Hadith, which are based on: representation , object (icon, index, and symbol), and interpretation (meaning of da'wah message) in JOYful Delight webtoon.